Relasi Romantis Yang Tidak Selalu Aman: Analisis Pelecehan Seksual Yang Terjadi Dalam Hubungan Pacaran - Dapurahayu, Sella; Jauharah, Sri Adisty; Dr.Hj.Asmak Ul Hosnah,SH.,MH. (PT. Sharia Journal and Education Center, 2024)
ABSTRACT This research examines the phenomenon of sexual harassment that occurs in dating relationships which is often hidden behind the label